Identitas nasional: Pengaruh media sosial terhadap identitas nasional Indonesia - Alfath, Alisa (Maliki Interdisciplinary Journal, 2025)
This study examines the impact of social media on Indonesian national identity. The widespread phenomenon of social media use in Indonesia has created a new communication environment with the potential to influence how individuals understand and express their national identity. Through in-depth interviews with social media users from various backgrounds, the research findings indicate that social media has a dual impact on national identity. On one hand, social media serves as a positive platform to strengthen national identity by disseminating information about history, culture, language, and national symbols that can be widely accessed, especially by the younger generation. It enables more inclusive public discussions about national values and provides a virtual space to express patriotism. On the other hand, social media also acts as a channel for foreign content that can blur local values and trigger shifts in identity, particularly when not accompanied by adequate digital literacy. Therefore, a strategic approach is needed to wisely utilize social media to reinforce national identity in the era of globalization.